Factors affecting the technical efficiency of potato production under the command area of the PMAMP project in Nepal: The case of Bajhang district - Shikshit Parajuli; Rabin Thapa (Cogent Food & Agriculture)
With the trend of decreasing productivity in agriculture, the Government of Nepal endorsed a special project, the Prime Minister Agriculture Modernization Project (PMAMP), in 2015. The project selected Bajhang district as the potato zone to boost the production and productivity of potatoes. Against this background, we determined the technical efficiency of potato production and the socio-economic variables determining the frontier using six local levels of Bajhang. The study surveyed a total of 101 households, which were randomly selected following a purposive sampling. This study employed a one-step stochastic frontier method to determine the technical efficiency of potato production in the district. The results revealed that potato production in the district under the command area of the potato zone was technically efficient at 87.75%. The significant elements of the technical inefficiency were years of schooling, access to credit, extension agent visits and receiving training. Thus, the inefficiency of 12.25% can be bridged by focusing and targeting the significant socio-economic aspects. Furthermore, the inefficiency can be reduced by increasing the usage of inputs like fertilizers, labor, farm size, and seeds, which had positive coefficients while the model suggests decreasing the usage of bullocks in potato cultivation. The return to scale was 0.898, revealing the decreasing nature of returns to production. These findings can be used by policy makers, practitioners, PMAMP and concerned stakeholders to increase the efficiency of potato production.